Method for regenerating activated carbon from waste tire carbon black
By mixing bamboo powder, composite nanomaterials and waste tire carbon black, a high porosity reactive carbon is formed, which solves the problems of low porosity and poor adsorption stability in activated carbon regeneration technology, and achieves efficient adsorption and environmentally friendly resource reuse .
Patent Information
- Application Number
- CN202411361363.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
AI Technical Summary
Among the existing activated carbon regeneration technology, the porosity of activated carbon is low, which leads to the easy desorption of adsorbed pollutants and may cause secondary pollution, and incineration treatment wastes resources and pollutes the environment.
Use bamboo powder, composite nanomaterials and waste tire carbon black to form high porosity reactive carbon, and use the steps of drying, carbonization, activation, hydrothermal crystallization and ultrasonic dispersion to improve the mesh honeycomb structure of composite nanomaterials. Adsorption stability and avoid contact between contaminants.
The specific surface area and porosity of activated carbon are improved, the adsorption efficiency is enhanced, the desorption of polluting substances is reduced, secondary pollution is avoided, and environmentally friendly resource reuse is achieved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of activated carbon processing, in particular to a method for regenerating activated carbon from waste tire carbon black. Background Art
[0002] Activated carbon adsorbent is a functional carbon material with well-developed pores, large specific surface area and strong adsorption capacity. Its acid, alkali and heat resistance make it widely used in various fields such as industry, agriculture, national defense, transportation, medicine and health, and environmental protection. It plays an increasingly important role in protecting the human living environment. However, after the activated carbon adsorption is saturated, it loses its purification ability, which not only easily produces a large amount of waste activated carbon, but also easily forms solid (hazardous) waste when the adsorption pollution source is different. It is reported that the annual amount of hazardous waste generated in the country is 60 million tons at this stage, of which waste activated carbon accounts for 65%, and the amount used for environmental pollution control accounts for 31.2% of the total amount of activated carbon, that is, the amount of waste activated carbon generated is 112,300 tons. These activated carbons are incinerated and destroyed after saturation, which greatly wastes resources and pollutes the environment. Therefore, the regeneration of activated carbon is particularly critical. The treatment effect of regenerated activated carbon is the same as that of new carbon, and the activated carbon can be regenerated many times, can be used for a long time, and can be used repeatedly, which greatly reduces the production cost and increases the economic benefit. Moreover, there is no unpleasant smell during the processing, and during transportation, space packaging is used, so there is no environmental pollution problem such as sewage leakage. It is a completely environmentally friendly product.
[0003] For example, the invention patent with announcement number CN103230785A discloses a method for producing regenerated activated carbon, the key steps of which include: placing waste activated carbon with a moisture content of 50% to 85% into a CNC high-temperature stewing furnace, and heating it at a temperature of 100 to 150°C for 3 to 7 hours; controlling the CNC high-temperature stewing furnace to gradually increase the temperature from 150°C to 900°C within 3 to 7 hours; introducing oxidizing gas into the CNC high-temperature stewing furnace for gasification reaction, controlling the temperature at 900-950°C, and maintaining it for 5 to 7 hours to obtain activated activated carbon; this step produces The high-temperature tail gas is re-introduced into step ②; the activated carbon is passed through a water cooling treatment system and cooled to 30°C after 5 to 7 hours; the regenerated activated carbon activation stage of the regenerated activated carbon production method is mainly completed in a high-temperature stewing furnace, with a high degree of automation, saving labor costs, and at the same time, the quality of the regenerated activated carbon produced is guaranteed, the energy consumption is low, and the pollution is reduced; however, the activated carbon prepared by this process has a low porosity, and the pollutants adsorbed in the later stage are easy to desorb, and the pollutants are directly mixed and contacted with each other, and are easy to react, thereby causing secondary pollution. Summary of the invention
[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a method for regenerating activated carbon from waste tire carbon black.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for regenerating activated carbon from waste tire carbon black, comprising the following steps:
[0007] 1) mixing bamboo powder, composite nanomaterials and waste tire carbon black, drying, and then carbonizing in a tubular furnace under nitrogen protection for 2-4 hours, and then introducing carbon dioxide gas and activating at a constant temperature for 24-36 hours to obtain an activated product;
[0008] 2) Add the activated product to an aqueous sodium hydroxide solution, react at 60-70°C for 12-15h, then stand at room temperature for 15-20h, then hydrothermally crystallize at 90-95°C for 24-30h, then ultrasonically disperse, filter, wash the filter residue with deionized water for 5-10 times, then dry the filter residue, put it in a tubular furnace, and carbonize it under inert gas protection for 3-7h to obtain regenerated activated carbon.
[0009] As a further preferred embodiment of the present invention, in step 1), the bamboo powder, the composite nanomaterial, and the waste tire carbon black are respectively 100-150 parts, 20-26 parts, and 200-300 parts by weight;
[0010] The carbonization temperature is 850-900°C.
[0011] As a further preferred embodiment of the present invention, in step 2), the concentration of the sodium hydroxide aqueous solution is 0.1-0.2 mol / L;
[0012] The carbonization temperature is 550-570°C.
[0013] As a further preferred embodiment of the present invention, the preparation method of the composite nanomaterial is as follows:
[0014] 1) Weigh chromium nitrate nonahydrate, terephthalic acid and concentrated hydrochloric acid, add to deionized water, then add porous nanofiber material, stir magnetically for 30-50 minutes, then place in a hydrothermal reactor, and react at 200-230° C. for 12-15 hours;
[0015] 2) After the reaction is completed, slowly cool to room temperature, centrifuge the product, collect the precipitate, add N,N-dimethylformamide to it, heat and purify it for 24-30 hours, centrifuge again to collect the precipitate, add anhydrous ethanol to it, heat and purify it for 24-30 hours, centrifuge to obtain the product, and dry it to obtain the desired composite nanomaterial.
[0016] As a further preferred embodiment of the present invention, the usage ratio of the chromium nitrate nonahydrate, terephthalic acid, concentrated hydrochloric acid, deionized water, porous nanofiber material, N,N-dimethylformamide, and anhydrous ethanol is (4-7) g: (1.5-2.0) g: (1-2) mL: (50-80) mL: (200-500) mg: (50-70) mL: (50-70) mL;
[0017] The concentration of the concentrated hydrochloric acid is 12-14 mol / L.
[0018] As a further preferred embodiment of the present invention, the rotation speed of the magnetic stirring is 900-1300 r / min;
[0019] The temperature of the heating purification is 80-86°C.
[0020] As a further preferred embodiment of the present invention, the preparation method of the porous nanofiber material is as follows:
[0021] 1) adding polyvinyl alcohol to deionized water, heating in a water bath to 80-85° C. and stirring evenly to obtain a polyvinyl alcohol solution, then adding tetraethyl silicate to the deionized water, and then adding phosphoric acid, stirring well to obtain a tetraethyl silicate solution, then mixing the polyvinyl alcohol solution and the tetraethyl silicate solution, adding nano-silicon dioxide and polystyrene nano-microspheres, and mixing evenly to obtain a spinning solution;
[0022] 2) electrospinning the spinning solution, and after the spinning is completed, placing the product in a muffle furnace, heating it to 650-750° C. at 5-8° C. / min in an air atmosphere, calcining it for 30-50 min, and then naturally cooling it to room temperature to obtain silica nanofibers;
[0023] 3) 10-15g of silica nanofibers are immersed in 100-160mL of 3-aminopropyltriethoxysilane ethanol solution for 30-50min, then washed repeatedly with anhydrous ethanol and dried, and then placed in 180-300mL of zinc nitrate ethanol solution for 10-30min, and then 30-60mL of 2-methylimidazole ethanol solution is slowly poured into the zinc nitrate ethanol solution, loaded at room temperature for 8-12h, and then washed repeatedly with anhydrous ethanol and dried, and then immersed in 80-130mL of n-butanol aqueous solution for 10-30min, and then immersed in 120-190mL of potassium permanganate aqueous solution, and reacted at 60-65°C for 2-5h, and then repeatedly rinsed with deionized water and dried to obtain a porous nanofiber material.
[0024] As a further preferred embodiment of the present invention, in step 1), in the polyvinyl alcohol solution, the ratio of polyvinyl alcohol to deionized water is (2-5) g: (18-30) mL;
[0025] In the tetraethyl silicate solution, the usage ratio of tetraethyl silicate, deionized water and phosphoric acid is (8.0-8.6) g: (7-10) mL: (0.04-0.05) g;
[0026] In the spinning solution, the usage ratio of polyvinyl alcohol solution, tetraethyl silicate solution, nano silicon dioxide and polystyrene nano microspheres is (50-70) g: (50-70) g: (2-5) g: (10-30) g.
[0027] As a further preferred embodiment of the present invention, in step 2), in the electrospinning, the electrostatic voltage is 20-25 kV, the spinning rate is 0.8-1.0 mL / h, the spinning distance is 15-18 cm, and the spinning time is 12-18 h.
[0028] As a further preferred embodiment of the present invention, in step 3), the concentration of the 3-aminopropyltriethoxysilane ethanol solution is 1-3wt%;
[0029] The concentration of the zinc nitrate ethanol solution is 3-7wt%;
[0030] The concentration of the 2-methylimidazole ethanol solution is 2-5wt%;
[0031] The concentration of the n-butanol aqueous solution is 0.4-0.8 mol / L;
[0032] The concentration of the potassium permanganate aqueous solution is 0.2-0.5 mol / L.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] In the present invention, polyvinyl alcohol and tetraethyl silicate are used as raw materials to prepare silica sol through sol-gel, then the silica sol is used as a substrate and polystyrene nanospheres are used as a pore-forming agent to obtain a precursor solution, and the silica nanofibers with a mesoporous structure are obtained through electrostatic spinning and high-temperature calcination, and then ZIF-8 nanoparticles are grown on the silica nanofibers through a hydrothermal in-situ growth method, and birnessite-type manganese dioxide is synthesized by an in-situ synthesis method, so as to obtain a porous nanofiber material; then chromium nitrate nonahydrate and terephthalic acid are used as raw materials to obtain a chromium metal organic framework material through a hydrothermal method, and the chromium metal organic framework material is combined with the porous nanofiber material through a high-temperature hydrothermal reaction method, so as to obtain a composite nanomaterial; the porous nanofiber material is combined with the chromium metal organic framework material through a high-temperature hydrothermal reaction method, so as to obtain a composite nanomaterial. The frame materials are combined with each other to form an interwoven mesh honeycomb structure inside the frame material, thereby providing an interception space for the subsequently adsorbed pollutants and preventing them from desorbing easily, thereby improving the stability after adsorption. At the same time, the formed mesh honeycomb structure can separate the adsorbed pollutants to avoid contact and reaction between different pollutants. At the same time, by blending the composite nanomaterial with bamboo powder and waste tire carbon black and then calcining and carbonizing them, the composite nanomaterial plays the role of a supporting skeleton. On the one hand, it can increase the porosity of the formed activated carbon and enhance the adsorption efficiency of the activated carbon. On the other hand, it can avoid the collapse of the internal voids during the calcination process, which is beneficial to maintain the stability and integrity of the void structure, so that the activated carbon achieves a high porosity.
[0035] The regenerated activated carbon in the present invention has high specific surface area, micropore volume and total pore volume, reduced micropore ratio, high adsorption rate for pollutants, and the adsorbed pollutants are not easy to desorb and can stably exist in the activated carbon without secondary pollution, so it has extremely strong practicality. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] A method for regenerating activated carbon from waste tire carbon black, comprising the following steps:
[0039] 1) According to weight parts, 100 parts of bamboo powder, 20 parts of composite nanomaterials, and 200 parts of waste tire carbon black are mixed, dried, and then carbonized at 850° C. for 2 hours in a tubular furnace under nitrogen gas protection, and then carbon dioxide gas is introduced and activated at a constant temperature for 24 hours to obtain an activated product;
[0040] 2) Add the activated material to a sodium hydroxide aqueous solution with a concentration of 0.1 mol / L, react at 60°C for 12 hours, then stand at room temperature for 15 hours, then hydrothermally crystallize at 90°C for 24 hours, then ultrasonically disperse, filter, wash the filter residue with deionized water 5 times, then dry the filter residue, put it into a tubular furnace, and carbonize it at 550°C for 3 hours under the protection of inert gas to obtain regenerated activated carbon.
[0041] Wherein, the preparation method of composite nanomaterial is as follows:
[0042] 1) adding 2 g of polyvinyl alcohol to 18 mL of deionized water, heating in a water bath to 80° C. and stirring uniformly to obtain a polyvinyl alcohol solution, then adding 8 g of tetraethyl silicate to 7 mL of deionized water, and then adding 0.04 g of phosphoric acid, stirring fully to obtain a tetraethyl silicate solution, then mixing 50 g of the polyvinyl alcohol solution and 50 g of the tetraethyl silicate solution, adding 2 g of nano-silicon dioxide and 10 g of polystyrene nanospheres, and mixing uniformly to obtain a spinning solution;
[0043] 2) electrospinning the spinning solution for 12 h under the conditions of an electrostatic voltage of 20 kV, a spinning rate of 0.8 mL / h, and a nozzle distance of 15 cm. After the spinning is completed, the product is placed in a muffle furnace, heated to 650 ° C at 5 ° C / min in an air atmosphere, calcined for 30 min, and then naturally cooled to room temperature to obtain silica nanofibers;
[0044] 3) 10 g of silica nanofibers were immersed in 100 mL of 1 wt% 3-aminopropyltriethoxysilane ethanol solution for 30 min, then washed repeatedly with anhydrous ethanol and dried, then placed in 180 mL of 3 wt% zinc nitrate ethanol solution for 10 min, then 30 mL of 2 wt% 2-methylimidazole ethanol solution was slowly poured into the zinc nitrate ethanol solution, loaded at room temperature for 8 h, then washed repeatedly with anhydrous ethanol and dried, then immersed in 80 mL of 0.4 mol / L n-butanol aqueous solution for 10 min, then immersed in 120 mL of 0.2 mol / L potassium permanganate aqueous solution, reacted at 60° C. for 2 h, rinsed repeatedly with deionized water and dried to obtain a porous nanofiber material;
[0045] 4) Weigh 4 g of chromium nitrate nonahydrate, 1.5 g of terephthalic acid and 1 mL of 12 mol / L concentrated hydrochloric acid, add them to 50 mL of deionized water, then add 200 mg of porous nanofiber material, stir magnetically at 900 r / min for 30 min, then place in a hydrothermal reactor and react at 200 ° C for 12 h;
[0046] 5) After the reaction is completed, slowly cool to room temperature, centrifuge the product, collect the precipitate, add 50 mL of N,N-dimethylformamide, heat and purify at 80°C for 24 hours, centrifuge again to collect the precipitate, add 50 mL of anhydrous ethanol, heat and purify at 80°C for 24 hours, centrifuge to obtain the product, and dry it to obtain the desired composite nanomaterial.
[0047] Example 2
[0048] A method for regenerating activated carbon from waste tire carbon black, comprising the following steps:
[0049] 1) According to weight parts, 120 parts of bamboo powder, 25 parts of composite nanomaterials, and 260 parts of waste tire carbon black are mixed, dried, and then carbonized at 870° C. for 3 hours in a tubular furnace under nitrogen gas protection, and then carbon dioxide gas is introduced and activated at a constant temperature for 30 hours to obtain an activated product;
[0050] 2) Add the activated material to a sodium hydroxide aqueous solution with a concentration of 0.15 mol / L, react at 65°C for 13 hours, then stand at room temperature for 18 hours, then hydrothermally crystallize at 93°C for 28 hours, then ultrasonically disperse, filter, wash the filter residue with deionized water 8 times, then dry the filter residue, put it into a tubular furnace, and carbonize it at 560°C for 5 hours under inert gas protection to obtain regenerated activated carbon.
[0051] Wherein, the preparation method of composite nanomaterial is as follows:
[0052] 1) adding 3 g of polyvinyl alcohol to 25 mL of deionized water, heating in a water bath to 83° C. and stirring uniformly to obtain a polyvinyl alcohol solution, then adding 8.5 g of tetraethyl silicate to 8 mL of deionized water, and then adding 0.05 g of phosphoric acid, stirring fully to obtain a tetraethyl silicate solution, then mixing 60 g of the polyvinyl alcohol solution and 60 g of the tetraethyl silicate solution, adding 3 g of nano-silicon dioxide and 20 g of polystyrene nano-microspheres, and mixing uniformly to obtain a spinning solution;
[0053] 2) electrospinning the spinning solution for 15 h under the conditions of an electrostatic voltage of 23 kV, a spinning rate of 0.9 mL / h, and a nozzle distance of 17 cm. After the spinning is completed, the product is placed in a muffle furnace, heated to 700 ° C at 7 ° C / min in an air atmosphere, calcined for 40 min, and then naturally cooled to room temperature to obtain silica nanofibers;
[0054] 3) 13 g of silica nanofibers were immersed in 150 mL of 2 wt% 3-aminopropyltriethoxysilane ethanol solution for 40 min, then washed repeatedly with anhydrous ethanol and dried, then placed in 240 mL of 5 wt% zinc nitrate ethanol solution for 20 min, then 40 mL of 4 wt% 2-methylimidazole ethanol solution was slowly poured into the zinc nitrate ethanol solution, loaded at room temperature for 10 h, then washed repeatedly with anhydrous ethanol and dried, then immersed in 100 mL of 0.6 mol / L n-butanol aqueous solution for 20 min, then immersed in 170 mL of 0.3 mol / L potassium permanganate aqueous solution, reacted at 62° C. for 3 h, rinsed repeatedly with deionized water and dried to obtain a porous nanofiber material;
[0055] 4) Weigh 5 g of chromium nitrate nonahydrate, 1.7 g of terephthalic acid and 1.5 mL of 13 mol / L concentrated hydrochloric acid, add them to 70 mL of deionized water, then add 400 mg of porous nanofiber material, stir magnetically at 1200 r / min for 40 min, then place in a hydrothermal reactor and react at 210 ° C for 13 h;
[0056] 5) After the reaction is completed, slowly cool to room temperature, centrifuge the product, collect the precipitate, add 60 mL of N,N-dimethylformamide, heat and purify at 85°C for 28 hours, centrifuge again to collect the precipitate, add 60 mL of anhydrous ethanol, heat and purify at 85°C for 28 hours, centrifuge to obtain the product, and dry it to obtain the desired composite nanomaterial.
[0057] Example 3
[0058] A method for regenerating activated carbon from waste tire carbon black, comprising the following steps:
[0059] 1) According to weight parts, 150 parts of bamboo powder, 26 parts of composite nanomaterials, and 300 parts of waste tire carbon black are mixed, dried, and then carbonized at 900° C. for 4 hours in a tubular furnace under nitrogen gas protection, and then carbon dioxide gas is introduced and activated at a constant temperature for 36 hours to obtain an activated product;
[0060] 2) Add the activated material to a 0.2 mol / L sodium hydroxide aqueous solution, react at 70°C for 15 hours, then stand at room temperature for 20 hours, then hydrothermally crystallize at 95°C for 30 hours, then ultrasonically disperse, filter, wash the filter residue with deionized water 10 times, then dry the filter residue, put it into a tubular furnace, and carbonize it at 570°C for 7 hours under inert gas protection to obtain regenerated activated carbon.
[0061] Wherein, the preparation method of composite nanomaterial is as follows:
[0062] 1) adding 5 g of polyvinyl alcohol to 30 mL of deionized water, heating in a water bath to 85° C. and stirring uniformly to obtain a polyvinyl alcohol solution, then adding 8.6 g of tetraethyl silicate to 10 mL of deionized water, and then adding 0.05 g of phosphoric acid, stirring fully to obtain a tetraethyl silicate solution, then mixing 70 g of the polyvinyl alcohol solution and 70 g of the tetraethyl silicate solution, adding 5 g of nano-silicon dioxide and 30 g of polystyrene nano-microspheres, and mixing uniformly to obtain a spinning solution;
[0063] 2) electrospinning the spinning solution for 18 h under the conditions of an electrostatic voltage of 25 kV, a spinning rate of 1.0 mL / h, and a spinning distance of 18 cm. After the spinning is completed, the product is placed in a muffle furnace, heated to 750 ° C at 8 ° C / min in an air atmosphere, calcined for 50 min, and then naturally cooled to room temperature to obtain silica nanofibers;
[0064] 3) 15 g of silica nanofibers were immersed in 160 mL of 3 wt % 3-aminopropyltriethoxysilane ethanol solution for 50 min, then washed repeatedly with anhydrous ethanol and dried, then placed in 300 mL of 7 wt % zinc nitrate ethanol solution for 30 min, then 60 mL of 5 wt % 2-methylimidazole ethanol solution was slowly poured into the zinc nitrate ethanol solution, loaded at room temperature for 12 h, then washed repeatedly with anhydrous ethanol and dried, then immersed in 130 mL of 0.8 mol / L n-butanol aqueous solution for 30 min, then immersed in 190 mL of 0.5 mol / L potassium permanganate aqueous solution, reacted at 65° C. for 5 h, rinsed repeatedly with deionized water and dried to obtain a porous nanofiber material;
[0065] 4) Weigh 7 g of chromium nitrate nonahydrate, 2.0 g of terephthalic acid and 2 mL of 14 mol / L concentrated hydrochloric acid, add them to 80 mL of deionized water, then add 500 mg of porous nanofiber material, stir magnetically at 1300 r / min for 50 min, then place in a hydrothermal reactor and react at 230 ° C for 15 h;
[0066] 5) After the reaction is completed, slowly cool to room temperature, centrifuge the product, collect the precipitate, add 70 mL of N,N-dimethylformamide, heat and purify at 86°C for 30 h, centrifuge again to collect the precipitate, add 70 mL of anhydrous ethanol, heat and purify at 86°C for 30 h, centrifuge to obtain the product, and dry it to obtain the desired composite nanomaterial.
[0067] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain composite nanomaterials.
[0068] Comparative Example 2: This comparative example is basically the same as Example 1, except that in the preparation of the composite nanomaterial, steps 1)-2) are omitted.
[0069] Comparative Example 3: This comparative example is basically the same as Example 1, except that step 3) is omitted in the preparation of the composite nanomaterial.
[0070] Comparative Example 4: This comparative example is basically the same as Example 1, except that in the preparation of the composite nanomaterial, steps 1) to 3) are omitted.
[0071] Comparative Example 5: This comparative example is basically the same as Example 1, except that in the preparation of the composite nanomaterial, steps 4)-5) are omitted.
[0072] Test experiment:
[0073] The process methods provided in Examples 1-3 and Comparative Examples 1-5 were respectively used to obtain regenerated activated carbon samples, and then the mixed gas adsorption performance was tested. The mixed gas consisted of dimethyl disulfide and methyl sulfide in a volume ratio of 1:1; the regenerated activated carbons after the test were placed in a vacuum box at 100°C for 24 hours, and the vacuum box was measured to determine whether there was a mixed gas. The results are shown in Table 1.
[0074] The adsorption rate test adopts: using standard gas in steel cylinders filled with nitrogen, dimethyl sulfide and dimethyl disulfide respectively, passing through a pressure reducing valve and then passing through a mass flow meter to control the flow rate, and then entering a gas mixing bottle for mixing, and the mixed gas is passed into a glass tube bed filled with modified activated carbon. Other conditions refer to the provisions of the national standard "GB / T12496.5-1999" (Test method for wood activated carbon - Determination of carbon tetrachloride adsorption rate (activity)), including gas flow rate, adsorption glass tube bed temperature, gas flow rate, test time, activated carbon adsorption rate calculation method and other related contents.
[0075] Table 1
[0076] Example 1 Example 2 Example 3 Comparative Example 1 Adsorption rate % 45.7 46.9 46.1 31.2 Mixed gas No mixed gas No mixed gas No mixed gas Contains mixed gas Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Adsorption rate % 40.2 38.1 33.6 34.9 Mixed gas Contains mixed gas Contains mixed gas Contains mixed gas Contains mixed gas
[0077] It can be seen from Table 1 that the regenerated activated carbon in the present invention not only has a high adsorption rate, but also the adsorbed gas can be stably present in the activated carbon, is not easy to desorb, and will not cause secondary pollution.
[0078] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for regenerating activated carbon from waste tire carbon black, characterized in that: The specific steps include: 1) mixing bamboo powder, composite nanomaterials and waste tire carbon black, drying, and then carbonizing in a tubular furnace under nitrogen protection for 2-4 hours, and then introducing carbon dioxide gas and activating at a constant temperature for 24-36 hours to obtain an activated product; 2) Add the activated product to an aqueous sodium hydroxide solution, react at 60-70°C for 12-15h, then stand at room temperature for 15-20h, then hydrothermally crystallize at 90-95°C for 24-30h, then ultrasonically disperse, filter, wash the filter residue with deionized water for 5-10 times, then dry the filter residue, put it in a tubular furnace, and carbonize it under inert gas protection for 3-7h to obtain regenerated activated carbon.
2. The method for regenerating activated carbon from waste tire carbon black according to claim 1, characterized in that: In step 1), the bamboo powder, the composite nanomaterial, and the waste tire carbon black are respectively 100-150 parts, 20-26 parts, and 200-300 parts by weight; The carbonization temperature is 850-900°C.
3. The method for regenerating activated carbon from waste tire carbon black according to claim 1, characterized in that: In step 2), the concentration of the sodium hydroxide aqueous solution is 0.1-0.2 mol / L; The carbonization temperature is 550-570°C.
4. The method for regenerating activated carbon from waste tire carbon black according to claim 1, characterized in that: The preparation method of the composite nano material is as follows: 1) Weigh chromium nitrate nonahydrate, terephthalic acid and concentrated hydrochloric acid, add to deionized water, then add porous nanofiber material, stir magnetically for 30-50 minutes, then place in a hydrothermal reactor, and react at 200-230° C. for 12-15 hours; 2) After the reaction is completed, slowly cool to room temperature, centrifuge the product, collect the precipitate, add N,N-dimethylformamide to it, heat and purify it for 24-30 hours, centrifuge again to collect the precipitate, add anhydrous ethanol to it, heat and purify it for 24-30 hours, centrifuge to obtain the product, and dry it to obtain the desired composite nanomaterial.
5. The method for regenerating activated carbon from waste tire carbon black according to claim 4, characterized in that: The usage ratio of the chromium nitrate nonahydrate, terephthalic acid, concentrated hydrochloric acid, deionized water, porous nanofiber material, N,N-dimethylformamide, and anhydrous ethanol is (4-7) g: (1.5-2.0) g: (1-2) mL: (50-80) mL: (200-500) mg: (50-70) mL: (50-70) mL; The concentration of the concentrated hydrochloric acid is 12-14 mol / L.
6. The method for regenerating activated carbon from waste tire carbon black according to claim 4, characterized in that: The rotation speed of the magnetic stirring is 900-1300r / min; The temperature of the heating purification is 80-86°C.
7. The method for regenerating activated carbon from waste tire carbon black according to claim 4, characterized in that: The preparation method of the porous nanofiber material is as follows: 1) adding polyvinyl alcohol to deionized water, heating in a water bath to 80-85° C. and stirring evenly to obtain a polyvinyl alcohol solution, then adding tetraethyl silicate to the deionized water, and then adding phosphoric acid, stirring well to obtain a tetraethyl silicate solution, then mixing the polyvinyl alcohol solution and the tetraethyl silicate solution, adding nano-silicon dioxide and polystyrene nano-microspheres, and mixing evenly to obtain a spinning solution; 2) electrospinning the spinning solution, and after the spinning is completed, placing the product in a muffle furnace, heating it to 650-750° C. at 5-8° C. / min in an air atmosphere, calcining it for 30-50 min, and then naturally cooling it to room temperature to obtain silica nanofibers; 3) 10-15g of silica nanofibers are immersed in 100-160mL of 3-aminopropyltriethoxysilane ethanol solution for 30-50min, then washed repeatedly with anhydrous ethanol and dried, and then placed in 180-300mL of zinc nitrate ethanol solution for 10-30min, and then 30-60mL of 2-methylimidazole ethanol solution is slowly poured into the zinc nitrate ethanol solution, loaded at room temperature for 8-12h, and then washed repeatedly with anhydrous ethanol and dried, and then immersed in 80-130mL of n-butanol aqueous solution for 10-30min, and then immersed in 120-190mL of potassium permanganate aqueous solution, and reacted at 60-65°C for 2-5h, and then repeatedly rinsed with deionized water and dried to obtain a porous nanofiber material.
8. The method for regenerating activated carbon from waste tire carbon black according to claim 7, characterized in that: In step 1), in the polyvinyl alcohol solution, the ratio of polyvinyl alcohol to deionized water is (2-5) g: (18-30) mL; In the tetraethyl silicate solution, the usage ratio of tetraethyl silicate, deionized water and phosphoric acid is (8.0-8.6) g: (7-10) mL: (0.04-0.05) g; In the spinning solution, the usage ratio of polyvinyl alcohol solution, tetraethyl silicate solution, nano silicon dioxide and polystyrene nano microspheres is (50-70) g: (50-70) g: (2-5) g: (10-30) g.
9. The method for regenerating activated carbon from waste tire carbon black according to claim 7, characterized in that: In step 2), in the electrospinning, the electrostatic voltage is 20-25 kV, the spinning rate is 0.8-1.0 mL / h, the spinning distance is 15-18 cm, and the spinning time is 12-18 h.
10. The method for regenerating activated carbon from waste tire carbon black according to claim 7, characterized in that: In step 3), the concentration of the 3-aminopropyltriethoxysilane ethanol solution is 1-3wt%; The concentration of the zinc nitrate ethanol solution is 3-7wt%; The concentration of the 2-methylimidazole ethanol solution is 2-5wt%; The concentration of the n-butanol aqueous solution is 0.4-0.8 mol / L; The concentration of the potassium permanganate aqueous solution is 0.2-0.5 mol / L.